Tadrīs al-Mauđū’āt al-Tārīkhiyyah bi Istirātījiyyah al-Tilmizah al-Ma’rifiyyah wa Aṡaruhā ‘alā Taḥṣīl Țālibāti al-Șaffi al-Śāmin al-Asāsi: تدريس الموضوعات التاريخية باستراتيجية التلمذة المعرفية وأثرها على تحصيل طالبات الصف الثامن الأساسي - Ahmed, Qazi Mosa; Ibrahim, Azhar Ali Hussein; Yousif, Falah Faqa (Study Program of Arabic Language Teaching, 2025)
This study aimed to investigate the effect of teaching historical topics using cognitive apprenticeship strategy on the academic achievement of eighth grade basic female students. The researchers adopted an experimental methodology with a post-test equivalent groups design. The research sample consisted of (60) female students from Dimen Girls' School affiliated with Zakho Education Directorate, randomly distributed into two groups: experimental group (30) students who studied historical topics using cognitive apprenticeship strategy, and control group (30) students who studied the same topics using conventional method. An achievement test in historical topics consisting of (20) multiple-choice items was prepared, and its validity and reliability were verified. The teaching of historical topics using the specified strategy was implemented during the first semester of the academic year (2024-2025) for nine weeks. The results showed that teaching historical topics using cognitive apprenticeship strategy achieved a statistically significant difference at the level (0.05) in favor of the experimental group in achievement, where the calculated t-value reached (3.166) and the effect size (0.147), indicating a large effect of teaching historical topics using this strategy. The researchers recommend adopting cognitive apprenticeship strategy in teaching historical topics and training history teachers on its implementation.